Evaluation of a pre‐tied ligature loop for canine total lung lobectomy. Issue 4 (19th March 2019) - Cronin, Anna M.; Pustelnik, Sasja B.; Owen, Laura; Hall, Jon L.
Abstract: Objective: To determine the ability of a pre‐tied ligature loop (PLL) to create a seal against physiological airway pressures after total lung lobectomy and report outcomes in dogs requiring lung lobectomy. Study design: Ex vivo experimental randomized study and clinical case study. Sample population: Thirty cadaveric canine lung lobes and 5 client‐owned dogs. Methods: Thirty canine lung lobes from dogs weighing 22.5–35 kg were randomized to lobectomy with stapler, PLL, or suture ligation. After lobectomy, each bronchial stump was submerged in water, and the mainstem airway pressure was increased to 80 mm Hg. Leakage was compared between techniques. The PLL was subsequently used in 5 dogs (17–25 kg) with neoplastic disease requiring total lung lobectomy. Results: Two stapled and 4 sutured bronchial stumps leaked at supraphysiological pressures >15 mm Hg. One stapled bronchial stump failed at a physiological airway pressure (5 mm Hg). None of the PLL lobectomies leaked. The incidence of bronchial stump failures did not differ among techniques ( P  = .15). Lung lobectomy was performed successfully with the PLL in 5 clinical cases with no intraoperative or postoperative complications; median follow‐up time was 6 months. Conclusion: Bronchial ligation with the PLL reliably resisted physiological airway pressures and performed comparably to current standard techniques in cadavers. The PLL provided an adequate air and vascular seal in 5 clinical cases undergoing total lung lobectomy. Clinical relevance: Pre‐tied ligature loops provide an alternative method for total lung lobectomy in dogs.